METHANE CONVERSION RATE AND METHANE EMISSION FACTOR OF BUFFALO FED DIFFERENT LEVEL OF LOCAL YEAST CULTUR CONTAINING (Saccharomyces cereviciae) - S. Suryahadi; Agus R. Nugroho; Rizaldi Boer; Ahmad Bey (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1997)
Abstract is available in the full text (pdf format)